Robust feedback control of convective drying of particulate solids. (September 2018) - Bück, Andreas; Seidel, Carsten; Dürr, Robert; Neugebauer, Christoph
Highlights: Continuous convective drying of particulate materials is considered. Parametric uncertainties in the second drying period are addressed. Feedback controller providing robust stability and performance are designed. Application is exemplified for drying of baker's yeast pellets in fluidised beds. Very good performance in view of kinetic uncertainty and operating point. Abstract: This work considers robust control of continuous convective drying of particulate solids where the major process uncertainty lies in the kinetics of the second (falling-rate) drying period. Using the concept of normalised drying curve, for arbitrary shape of the curve, the steady state particle moisture content is derived. Applying appropriate uncertainty models, a robust feedback controller is designed to guarantee desired product moisture. Advantages of this approach are discussed in comparison to convential PI and LQ-optimal control. The approach is exemplified for the case of fluidised bed drying of baker's yeast particles. Results show very good performance with respect to parametric uncertainty and disturbance rejection even at non-nominal steady-states.